Dispersion Pattern of Giant Cicada (Hemiptera: Cicadidae) in a Brazilian Coffee Plantation - Andrade, S. C [UNESP]; Rossi, G. D [UNESP]; Martinelli, N. M [UNESP] (Oxford University Press (OUP), 2020)
The giant cicada Quesada gigas (Olivier, 1790) (Hemiptera: Cicadidae) is a major pest of coffee plants in Brazil. To ensure the rational management and ecological equilibrium, information about the behavior, dispersion, and reproduction of giant cicada is fundamental. The present work was conducted in an area of 97 ha planted with Coffea arabica L. to investigate adult dispersion as well as mating and oviposition behaviors of Q. gigas. A sound trap was placed at a 'release point' used for the attraction, marking, and release of adults in the area. The recapture of insects was performed with the same sound trap positioned at 20 points distributed at 100, 250, 400, and 1,000 m from the release point. The highest recapture rates of Q. gigas were observed at 100 m from the release point, and the lowest recapture rates were observed at 1,000 m. The presence of Eucalyptus plants in the area apparently influenced dispersion, as high recapture rates were observed at the sites close to Eucalyptus plants. One copulation of Q. gigas lasted 41.6 ± 0.43 min, and the period of a single oviposition bout was 30.0 ± 0.20 min. Quesada gigas adult longevity in the field was estimated to be 49 d. Both males and females were observed performing multiple matings.
Keywords: Coffea arabica; insect behavior; lek mating; multiple mating; Quesada gigas; sound trap